Optimizing Digital Interactive Boards (DIBs) in Building a Student-Centered Learning Ecosystem: An Analysis of Teacher Readiness and Adaptation - Rusma Yunita (Yayasan Sembilan Pemuda Indonesia, 2026)
This study analyzes the optimization of Digital Interactive Boards (DIBs) in building student centered learning ecosystems, focusing on teacher readiness and adaptation. A Systematic Literature Review (SLR) was conducted, synthesizing 15 peer-reviewed articles published between 2021 and 2026 from Scopus and ERIC databases. The findings reveal that DIB effectiveness is contingent upon three interrelated factors: (1) teacher readiness encompassing technological, pedagogical, and psychological dimensions; (2) a staged adaptation process moving from technical onboarding to pedagogical transformation; and (3) institutional support including ongoing training and collaborative school culture. The novelty of this study lies in its integrated framework linking teacher readiness analysis with student centered ecosystem development, shifting the discourse from technology adoption to human adaptation. Practically, the findings emphasize the need for sustained professional development programs, responsive technical infrastructure.